Identifikasi Flavonoid dalam Fraksi Kloroform Daun Binahong (Anredera cordifolia (Tenore) Steen) - Hanifah Karimatulhajj (Universitas Ngudi Waluyo, 2020)
ABSTRAKFraksi kloroform daun binahong dari ekstrak etanoliknya telah dilaporkan dapat mempercepat penyembuhan luka pada hewan uji. Penelitian ini merupakan kelanjutan dari penelitian sebelumnya untuk mengetahui keberadaan senyawa flavonoid dalam fraksi kloroform daun binahong dengan metode kromatografi lapis tipis. Ekstrak etanol daun binahong diawalemakkan dengan n-heksan kemudian difraksinasi dengan kloroform menggunakan metode fraksinasi cair-padat. Selanjutnya fraksi dielusi dengan fase gerak n-heksan:etil asetat:metanol dengan perbandingan 6:3:1 dan fase diam silica gel 60F254. Deteksi semprot menggunakan pereaksi sitroborat yang sensitif terhadap senyawa flavonoid. Hasil KLT menunjukkan adanya 11 spot pada fraksi kloroform daun binahong yang di dalamnya tidak terdapat senyawa flavonoid.Kata kunci : KLT, Fraksi Kloroform Daun Binahong, Flavonoid, Penyembuhan lukaChloroform fraction of madeira vine leaf (FKDB) from the ethanolic extract (EEDB) was reported could promotes wound healing on gentle rat wistar animal testing. Quercetin flavonoid is the one of phytochemical that has wound healing pharmacology activity. Quercetin was found in the shoot part of madeira vine plants. The Leaf was located at the shoot part of plant that might contain flavonoid. This study was conduct to determine contain of quercetin in madeira vine’s leaf especially at chloroform fraction. EEDB made with maseration method. Madeira vine’s leaf powder soaked with ethanol 96% for 4 days and stirred for 3 hours then soaked again. Filtrate was taken after 24 hours and repeated until 4 days with solvent replacement. The extract was concentrated using rotary evaporator at50o C until concentrated. The solven evaporated using waterbath at the same temperature. Extract was defatted with n-hexane and fracionated with chloroform using liquid-solid method until obtain FKDB. Identification of phytochemical compounds in the chloroform fraction of madeira vine’s leaves by thin layer chromatography method. The fraction eluted in saturated chamber using mobile phase mixture of n-hexan:ethyl asetate:methanol with comparison 6:3:1 and activated silica gel 60F254 as stationary phase. Spray detection using citroborat reagent which is sensitive to flavonoids. The result identificated using UV 254 and UV 366 showed that any 11 spot in the chloroform fraction of madeira vine’s leaves with no presense quercetin flavonoid there.